Peran Orang Tua dalam Perkembangan Tindak Tutur Anak Usia Dini - A Nurhayati; Rahmatia Rahmatia (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This research discusses the role of parents in the development of early childhood speech acts. The aim of this research is to investigate the role played by parents in the development of early childhood speech acts. This study was carried out using a qualitative approach by collecting data using observation, interviews and document analysis. The research participants consisted of ten families with children aged 3-5 years taken from various social and economic backgrounds. The research results show that the role of parents has a significant impact on the development of children's speech acts, including vocabulary formation, speaking abilities, and social communication patterns. Factors such as parent-child interactions, communication patterns within the family, and the social environment also influence the development of children's speech acts. The implication of these findings is the need for greater attention to the role of parents in supporting early childhood language and communication development through educational programs and social support for families.